Effect of Ag nanoparticles seeding on the properties of silica spheres. Issue 6 (15th April 2018) - Misran, H.; Salim, M.A.; Ramesh, S.
Abstract: In this study, the effect of seed-recrystallization on the Ag deposition onto silica sphere surfaces has been investigated. It was found that increasing the seed-recrystallization cycles resulted in higher atomic deposition at ca. 84% coverage of silica surfaces with the same mole ratio of Ag precursor characterized by the Ag/Si atomic ratio obtained by XPS analyses. The addition of straight-chain palm oil derived fatty alcohols (PODFA) in the sol-gel prior to seed-recrystallization aided the deposition of Ag. Thus, PODFA play the role of nonsurfactant surface modification agent to produce Ag-silica nanocomposite. Structural analyses showed that the resulting Ag nanocrystallines having a face centre cubic structure and particle size of 5–20 nm were deposited homogeneously on silica spheres. Chemical state analyses from XPS indicated that the increasing number of seed repetition process increased the seeding of Ag nanoparticles on silica surface with the same molar of Ag atoms. XPS spectra at O1s orbital elucidated that the binding energy of three oxides components were determined at ca. 533.8 eV (Si-O-H), 532.8 eV (Si-O-Si) and 530.8 eV (Si-O-Ag), respectively. The high sensitivity of surface plasmon resonance observed in the nanocomposites prepared in this study are useful in optical applications.